EFFECTIVENESS OF PERFORMANCE MEASUREMENT IN REALIZING WORLD-CLASS COMPANIES IN THE PERSPECTIVE OF MALCOLM BALDRIGE - Kartikawati, Windha Dwi; Munandar, Jono M.; Suprayitno, Gendut (Universitas Brawijaya, Indonesia, 2020)
The Superior Performance Assessment Criteria (KPKU) assessment is conducted annually by Perum Peruri in accordance with the Secretary of the Ministry of State Owned Entreprises (SOEs) number S-08 / S.MBU / 2013 concerning Submission of KPI Guidelines and Criteria for Superior Performance Assessment on SOEs. This research was conducted to analyze the KPKU's assessment of Perum Peruri whether it had been effectively carried out at Perum Peruri and to see the influence between the categories of KPKU. KPKU assessment of Perum Peruri data was analyzed using a t-test (one sample), trend analysis and structural equation modeling (SEM) partial least square (PLS) approach. Peruri KPKU value always increases every year, it indicates that the presence of Peruri KPKU can improve its performance. The results of the analysis with the T test that the Perum Peruri KPKU score has not been effective in achieving the Ministry of SOEs target, but if a trend analysis is carried out for the next 5 years the assessment score shows a positive upward trend, then for the SEM-PLS results it is known that all categories in the KPKU assessment are interrelated and influence. It is necessary to conduct further research related to the influence of KPKU categories to improve KPKU assessment scores.